THE INFLUENCE OF CORPORATE GOVERNANCE, COMPANY SIZE, AND LEVERAGE TOWARD EARNING MANAGEMENT - Mayasari Mayasari; Ayu Yuliandini; Intan Indah Permatasari (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2019)
The purpose of this study is to examine the influence of GCG variables, firm size, and leverage on earnings management. The sample used is 35 public listed property and real estatecompanies in the Indonesia Stock Exchange (IDX) from 2015 until 2017. The sampling technique uses purposive sampling. This study uses multiple regression. The results of the analysis showed that managerial ownership does not have a negative effect on earnings management but oppositely, it has a positive effect on earnings management, while company size does not have any effect on earning management.